МУЛЬТИКУЛЬТУРАЛІЗМ ЯК ПРИНЦИП ПОБУДОВИ СУЧАСНОГО СУСПІЛЬСТВА - Корнієнко, О. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті аналізується політика мультикультуралізму в сучасному поліетнічному суспільстві і доцільність її застосування в Україні. Не дивлячись на існуючі недоліки і помилки в реалізації мультикультуралізму, альтернативи йому в сучасному поліетнічному суспільстві, яке базується на за- садах гуманізму, свободи культурного самовираження, демократії, з точки зору автора, не існує. Корниенко А.Н. Мультикультурализм как принцип построения современного общества. В статье анализируется политика мультикультурализма в современном полиэтническом обществе и це- лесообразность ее применения в Украине. Несмотря на существующие недостатки и ошибки в реализа- ции мультикультуралтзма, альтернативы ему в современном полиэтническом обществе, основанном на принципах гуманизма, свободы культурного самовыражения, демократии, с точки зрения автора, не су- ществует. Ключевые слова: мультикультурализм, толерантность, нация, этногенез, гражданская идентич- ность, полиэтничность. Olexandr Korniyenko. Multiculturalism as a principle of modern society formation. The article analyzes the policy of multiculturalism in modern polyethnic society and the importance of its implementation in Ukraine. The crisis of the multiculturalism is that a state and a society exist in a variety of separate formations that live together but don’t cooperate and identify themselves as a united state. The way out is that a policy of a civil identity should become the basis of the state policy. Civil identity in the basis of the «western» model of the nation that considers nation as a polyethnic formation that unites people of different ethnic societies and is based on a political and is based on a political and juridical equality of its members. This model of the nation is the most favorable for Ukraine. From the point of the author’s view in spite of the drawbacks and mistakes made in the realization of multiculturalism there is no alternative for it in a modern polyethnic society that is based on the basis of humanism, freedom of cultural self-expression, democracy. It concerns Ukraine indeed. Keywords: multiculturalism, tolerance, nation, civil identity, ethnogenes, polyethnicity.